The Role of Family, School, and Society in Moral Development and Character Building Elementry School Age Children - Muhammad Hamdi; Sultoni Sultoni; Abdi Sukma (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: The development of moral values ​​and character in children is one area that needs attention. This study discusses how society, families, and schools can help children in primary schools develop moral character and moral values. Background Problems: Without parents' knowledge, moral ideals are taught to children, and character development does not occur naturally. It is essential for the community, schools, and parents to pay attention to how children in primary schools develop their character. A harmonious and dynamic environment must be built for children to create strong characters and good spirits in their families, schools and communities. Novelty: This research is a research, and the difference between previous research and the research conducted is that the earlier research did not integrate the three variables in one research title. Research Methods: This research uses a literature study as its research approach. Finding/Results: Children's moral development and character are strongly influenced by their families, schools and communities. However, family or parents are the most important factors because they are the first schools that prepare children for life in the real world. Conclusion: The role of parents, educators, and society is essential. The three of them, in instilling character, must work together. Strengthening character education today must continue to be improved. The three educational centres, namely parents, educators and the community, are good sources for academic development.